Expression of SNAIL in accompanying PanIN is a key prognostic indicator in pancreatic ductal adenocarcinomas. (21st February 2019) - Fujiwara, Sho; Saiki, Yuriko; Ishizawa, Kota; Fukushige, Shinichi; Yamanaka, Mie; Sato, Masaki; Ishida, Masaharu; Motoi, Fuyuhiko; Unno, Michiaki; Horii, Akira
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is the most lethal cancer, mainly because of its invasive and metastatic characteristics. Pancreatic intraepithelial neoplasia (PanIN) is one of the major precursor lesions of PDAC. Although epithelial‐to‐mesenchymal transition (EMT) is known to play an important role for these malignant behaviors, the association between PanIN and EMT has not been clearly understood. Therefore, we explored possible molecules for regulation of EMT immunohistochemically. Using surgically resected specimens from 71 PDAC patients, expressions of SNAIL, SLUG, TWIST1, and ZEB1 were investigated in high‐grade PanIN (HG‐PanIN) and PDAC. Results demonstrated that PDAC accompanied by SNAIL‐positive HG‐PanIN showed a significantly better relapse‐free survival (RFS) (median survival time (MST) of 11.3 months vs 4.4 months, P < 0.001) and overall survival overall survival (OS) (MST of 25.2 months vs 13.6 months, P < 0.001). In PDAC accompanied by SLUG‐positive HG‐PanIN, RFS and OS ( P = 0.09 and P = 0.05) tended to have a better prognosis. In contrast, we could not find any significant prognostic benefits in the expression of TWIST1 or ZEB1 in PDAC accompanied by HG‐PanIN. Our present results suggest that (1) EMT may play an important role in the development of PDAC from HG‐PanIN, and (2) SNAIL may predict a distinct subgroup that shows a better prognosis. Abstract : Epithelial‐to‐mesenchymal transition may play an important role in the development of pancreatic ductal adenocarcinoma from high‐grade pancreatic intraepithelial neoplasia, and SNAIL may predict a distinct subgroup that shows a better prognosis.